Drinking despite health problems among individuals with liver disease across the United States. (1st July 2017) - Elliott, Jennifer C.; Stohl, Malka; Hasin, Deborah S.
Highlights: We study predictors of drinking despite health problems in those with liver disease. We use a nationally representative sample of individuals with liver disease. Drug use and personality disorders predict drinking despite health problems. A family history of alcohol problems predicts drinking despite health problems. Liver disease patients with some psychiatric comorbidities may drink despite risks. Abstract: Background: Heavy drinking is harmful for individuals with liver disease. However, some of these individuals drink despite knowledge of the risks. The current study aims to identify factors underlying drinking despite health problems among individuals with liver disease. Methods: The current study utilizes a subsample of individuals reporting past-year liver disease and at least one drink in the past year (n = 331), taken from the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III), a large nationally representative survey of the United States. Participants reported on drinking despite health problems, symptoms of psychopathology, and family history of alcohol problems in a cross-sectional survey. Results: Drug use disorders (Adjusted Odds Ratio [AOR] = 2.68), as well as borderline, antisocial, and schizotypal personality disorders (AORs = 2.50–4.10), were associated with increased likelihood of drinking despite health problems among individuals with liver disease, all ps < 0.05. Any anxiety disorder trended toward significance (AOR = 2.22), p = 0.06, but major depressive disorder was not associated with increased risk, (AOR = 0.99), ps = 0.97. Individuals with a family history of alcohol problems were also more likely to drink despite health problems (AOR = 2.79), p < 0.05. Conclusions: Several types of psychopathology, as well as a family history of alcohol problems, increased the likelihood of drinking despite health problems among individuals with liver disease. These findings highlight the need to intervene with heavily drinking individuals with liver disease, who may be drinking due to familial risk and/or comorbid psychopathology.